Design of Lifter Flyover Segment with a Structure of Lifting Beam can Escape Pairs - Dhimas Satria; Aswata Aswata; Imron Rosyadi; Rina Lusiani; Erny Listijorini; Fadhil Arief (Universitas Sultan Ageng Tirtayasa, 2020)
The flyover development today is very much at all to do because it is one solution as degrading congestion and lifter segment flyover is one important tool in the construction of flyovers. This final project offers an example of the calculation and planning lifter segment fly over the beam structure for lifting can be separated pairs which can later be changed in accordance with the specification segment flyover to be lifted. The final project is expected to be one of the references manufacture segments lifter fly over. This design uses Pahl and Beitz method and the results of this research. Specifications lifter segment fly over with beam structure for lifting to be loose tide is Lifting Equipment; Wire rope with two types of options on each drum are strands left and right torsion. Mechanism trolley; Can move on the path along the 3,019 mm, diameter the wheel trolley 381 mm, Trolley the wheel shaft diameter: 12 cm or 120 mm with material JIS S45C. Struktur lifter; Beam lifting using a beam with a weight per unit length of 1.97 N / mm with JIS G3101 SS540 material along the 4900 mm and a surface area of retaining cylindrical pedestal A of 5024 mm2 with material JIS G3101 SS540. The mechanism of motion lifter can move on the path along the 4000 mm. Wheel lifter diameter 533.4 mm. Hydraulic of lifters driver using a double acting hydraulic with a maximum